Pre-sodium-modified sodium ion battery negative electrode material as well as preparation method and application thereof

By using high-temperature activation and chemical vapor deposition technology in the negative electrode material of sodium ion battery, a pre-sodium porous carbon structure is formed, which solves the problem of excessive sodium ion consumption during the first charge and discharge of sodium ion batteries, and achieves higher first-term efficiency and lower production costs.

CN119905539AActive Publication Date: 2025-04-29LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD

Patent Information

Application Number
CN202311420243.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

During the first charging and discharging process of the existing sodium ion battery negative electrode materials, the formation and side reaction of the SEI film cause excessive sodium ions to consume, which reduces the first effect of the battery, and the method of reducing ash and specific surface area cannot fundamentally solve the problem of sodium ions consumed by the SEI film, and the cost is increased.

Method used

By mixing the carbon precursor with sodium hydroxide and activate at high temperature, a pore structure is formed and high-active Na2O or Na is generated in the pores. The pore structure is then closed-porely treated by chemical vapor deposition to protect the high-active Na2O or Na, and achieve the pre-sodiumization effect, while reducing the specific surface area and reducing the formation of SEI film.

Benefits of technology

Effectively supplement sodium ions, reduce consumption of electrolyte, improve the first-effect problem of materials, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905539A_ABST
    Figure CN119905539A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a pre-sodium-modified sodium ion battery negative electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a carbon precursor and sodium hydroxide according to a certain mass ratio, and grinding to obtain mixed powder; in an inert atmosphere, putting the mixed powder into a rotary furnace for activating treatment so as to decompose sodium hydroxide and reduce the sodium hydroxide by carbon in the carbon precursor, and etching the carbon precursor so as to form a pore structure of the carbon precursor to obtain a pre-sodium porous carbon material; and in a rotary furnace, coating the pre-sodium porous carbon material through chemical vapor deposition to obtain the pre-sodium-modified sodium ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a pre-sodiumized sodium ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion battery is a secondary battery. Sodium and lithium belong to the same alkali metal group and have similar physical and chemical properties to lithium. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: abundant sodium resources, low cost, high energy density, and good temperature tolerance.

[0003] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, which mainly rely on the movement of sodium ions between the positive and negative electrodes. Similarly, during the initial charge and discharge process, the formation of the SEI film and the occurrence of side reactions will consume the sodium ions in the battery system, resulting in a reduction in the initial efficiency.

[0004] At present, the most common methods to improve the first efficiency are to reduce the ash content and reduce the specific surface area. Reducing the ash content can reduce the occurrence of side reactions and reduce the loss of sodium ions; reducing the specific surface area can reduce the contact area between the electrolyte and the electrode surface, reduce the formation area of ​​the solid electrolyte interface (SEI) film, and reduce the consumption of sodium ions. At the same time, the reduction in specific surface area can reduce the phenomenon that sodium ions enter smaller pore structures and cannot escape. Although reducing the ash content and reducing the specific surface area can improve the first efficiency to a certain extent, these two methods cannot fundamentally solve the sodium ions consumed by the formation of the SEI film, and the reduction of ash content and specific surface area is limited by the material itself. In addition, the commonly used method to reduce ash content is pickling. The increase in pickling process will sharply increase the cost of materials, which is not conducive to giving full play to the advantage of low manufacturing cost of sodium batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a pre-sodiumized sodium ion battery negative electrode material and a preparation method and application thereof in view of the defects existing in the prior art. The high-temperature activation process in the preparation method enables a carbon precursor to form a pore structure, and at the same time generates highly active Na2O or Na in the pores; chemical vapor deposition performs a closed-pore treatment on the pore structure to protect the highly active Na2O or Na in the pores, thereby achieving a pre-sodium effect, and at the same time reducing the specific surface area, reducing the generation of SEI film, and improving the first effect problem of the material.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a pre-sodiumized sodium ion battery negative electrode material, the preparation method comprising:

[0007] The carbon precursor and sodium hydroxide are mixed and ground according to a certain mass ratio to obtain a mixed powder;

[0008] Under an inert atmosphere, placing the mixed powder in a rotary kiln for activation treatment, so that the sodium hydroxide is decomposed and reduced by the carbon in the carbon precursor, and at the same time, etching the carbon precursor so that the carbon precursor forms a porous structure to obtain a pre-sodium porous carbon material;

[0009] In the rotary kiln, the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0010] Preferably, the mass ratio of the carbon precursor to sodium hydroxide is 1:10-5:1.

[0011] Preferably, the temperature of the activation treatment is 500° C.-1200° C., and the time of the activation treatment is 1 hour-12 hours.

[0012] Preferably, the carbon precursor includes walnut shell, coconut peel, nut shell, kelp, grapefruit peel, lotus root, eggshell membrane, cork, coconut shell, straw, starch, renewable cotton, polyaniline, lignin, cellulose, hemicellulose, honeycomb briquettes, chitosan, asphalt, phenolic resin, glucose, magnesium gluconate, polyvinyl pyrrolidone, graphene oxide, graphene, xylose, epoxy resin, petroleum coke or one or more products of the above substances after high-temperature treatment; wherein the temperature of the high-temperature treatment is 800°C-1800°C.

[0013] Preferably, the chemical vapor deposition gas includes a carbon source gas and a protective gas; wherein the volume ratio of the carbon source gas to the protective gas is 1:5-5:1.

[0014] Preferably, the carbon source gas is one or more of methane, acetylene, ethylene, propylene or carbon monoxide; and the protective gas is one or more of nitrogen, helium or argon.

[0015] Preferably, the chemical vapor deposition conditions are: deposition temperature 500° C.-900° C., deposition time 0.5 hour-12 hours.

[0016] In a second aspect, the present invention provides a pre-sodiumized sodium-ion battery negative electrode material, characterized in that the pre-sodiumized sodium-ion battery negative electrode material is prepared by any preparation method described in the first aspect above.

[0017] In a third aspect, the present invention provides a negative electrode plate, which includes the pre-sodiumized sodium ion battery negative electrode material described in the second aspect.

[0018] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the third aspect.

[0019] The preparation method of the pre-sodiumized sodium ion battery negative electrode material provided by the embodiment of the present invention achieves the effect of pre-sodiumization of the carbon-based negative electrode through mixed grinding, high temperature activation, chemical vapor deposition and other processes, wherein the high temperature activation and chemical vapor deposition are both carried out in a rotary furnace, so as to realize the continuity of the preparation process, reduce the complexity of the conversion between processes, and facilitate large-scale production. The activation process enables the carbon precursor to form a pore structure, and with the help of the by-products in the sodium hydroxide activation process, highly active Na2O or Na is generated in the pores to pre-sodiumize the negative electrode material. In this way, sodium ions can be supplemented, the sodium content in the battery system can be increased, the consumption of electrolyte can be reduced, and the consumption of sodium ions in the formation process of the solid electrolyte interface film can be compensated. The pore structure is closed by chemical vapor deposition to protect the highly active Na2O or Na in the pores, enhance the pre-sodium effect, and reduce the specific surface area, reduce the formation of SEI film, and improve the first effect problem of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flow chart of a method for preparing a pre-sodiumized sodium ion battery negative electrode material provided in an embodiment of the present invention;

[0021] Figure 2 The charge and discharge curves of button-type half-cells assembled in Examples 1-5 and Comparative Example 2 of the present invention;

[0022] Figure 3 The first effect data statistics of button-type half-cells assembled in Examples 1-5 of the present invention and Comparative Example 2 are shown;

[0023] Figure 4 This is a statistical chart of initial voltage data of button-type half-cells assembled in Examples 1-5 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0026] The present invention provides a method for preparing a pre-sodiumized sodium ion battery negative electrode material, the process of which is as follows: Figure 1 As shown, the following steps are included:

[0027] Step 110, mixing the carbon precursor and sodium hydroxide in a certain mass ratio and grinding to obtain a mixed powder;

[0028] Specifically, the mass ratio of the carbon precursor to sodium hydroxide can be 1:10-5:1, preferably 1:3. The carbon precursor can specifically include walnut shells, coconut skins, nut shells, kelp, grapefruit peels, lotus roots, eggshell membranes, corks, coconut shells, straw, starch, renewable cotton, polyaniline, lignin, cellulose, hemicellulose, honeycomb briquettes, chitosan, asphalt, phenolic resins, glucose, magnesium gluconate, polyvinyl pyrrolidone, graphene oxide, graphene, xylose, epoxy resins, petroleum coke, or one or more products of the above substances after high temperature treatment. Among them, the temperature of high temperature treatment can specifically be 800°C-1800°C.

[0029] Step 120, placing the mixed powder in a rotary kiln for activation treatment under an inert atmosphere, so that the sodium hydroxide is decomposed and reduced by the carbon in the carbon precursor, and at the same time, the carbon precursor is etched so that the carbon precursor forms a porous structure to obtain a pre-sodium porous carbon material;

[0030] Specifically, the inert atmosphere may include one or more of nitrogen, helium or argon. The temperature of the activation treatment may be 500°C-1200°C, preferably 800°C. The time of the activation treatment may be 1 hour-12 hours, preferably 6 hours. The air flow rate of the nitrogen gas may be 0.8L / min-1.2L / min, preferably 1L / min. The pre-sodium porous carbon material includes a carbon precursor and sodium oxide, sodium element, etc. located in the pore structure of the carbon precursor.

[0031] The chemical equation of the reaction that occurs during the activation treatment is as follows:

[0032] 2NaOH=Na2O+H2O

[0033] C+H2O=H2+CO

[0034] CO+H2O=H2+CO2

[0035]

[0036] C+Na2O=2Na+CO

[0037] It should be noted that the above chemical reaction equation only represents some chemical reactions that may occur during the activation process. For example, not all sodium oxide reacts with carbon to generate sodium element, and not all sodium oxide reacts with carbon dioxide to generate sodium carbonate.

[0038] The high-temperature activation process allows the carbon precursor to form a porous structure, and at the same time, with the help of the by-products of the decomposition process of sodium hydroxide, highly active Na2O or Na is generated in the pores.

[0039] Step 130, in a rotary kiln, coating the pre-sodium porous carbon material by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0040] Specifically, the gas for chemical vapor deposition may include a carbon source gas and a protective gas. The volume ratio of the carbon source gas to the protective gas is 1:5-5:1. The carbon source gas may be one or more of methane, acetylene, ethylene, propylene or carbon monoxide. The gas flow rate when the carbon source gas is introduced may be 0.1 L / min-1.0 L / min, preferably 0.8 L / min.

[0041] The protective gas may be one or more of nitrogen, helium or argon. The gas flow rate of the protective gas during introduction may be 0.1 L / min-1 L / min, preferably 0.2 L / min.

[0042] The conditions of chemical vapor deposition are as follows: the deposition temperature is specifically 500° C.-900° C., preferably 800° C.-900° C. The deposition time is specifically 0.5 hour-12 hours, preferably 1 hour-6 hours.

[0043] Chemical vapor deposition coats the pre-sodium porous carbon material to form a closed-pore structure, protecting the highly active Na2O or Na in the pores, enhancing the pre-sodium effect, while reducing the specific surface area and reducing the formation of SEI film.

[0044] As a preferred embodiment, if the carbon precursor has not been subjected to high-temperature treatment, in order to improve the carbonization effect, after step 130, the preparation method further includes: further subjecting the prepared pre-sodiumized sodium ion battery negative electrode material to high-temperature carbonization treatment, and the conditions of the high-temperature carbonization treatment are: the temperature can be specifically 800°C-2000°C, the time can be 1 hour-12 hours, and the inert atmosphere can be one or more of nitrogen, helium or argon.

[0045] Of course, it is understandable that the carbon precursor may also be subjected to high-temperature carbonization treatment before step 110 .

[0046] The preparation method of the pre-sodiumized sodium ion battery negative electrode material provided by the embodiment of the present invention achieves the effect of pre-sodiumization of the carbon-based negative electrode through mixed grinding, high temperature activation, chemical vapor deposition and other processes, wherein the high temperature activation and chemical vapor deposition are both carried out in a rotary furnace, so as to realize the continuity of the preparation process, reduce the complexity of the conversion between processes, and facilitate large-scale production. The activation process enables the carbon precursor to form a pore structure, and with the help of the by-products in the sodium hydroxide activation process, highly active Na2O or Na is generated in the pores to pre-sodiumize the negative electrode material. In this way, sodium ions can be supplemented, the sodium content in the battery system can be increased, the consumption of electrolyte can be reduced, and the consumption of sodium ions in the formation process of the solid electrolyte interface film can be compensated. The pore structure is closed by chemical vapor deposition to protect the highly active Na2O or Na in the pores, enhance the pre-sodium effect, and reduce the specific surface area, reduce the formation of SEI film, and improve the first effect problem of the material.

[0047] The pre-sodiumized sodium ion battery negative electrode material provided by the embodiment of the present invention can be applied to the electrode material of the sodium ion battery.

[0048] In order to better understand the technical solution provided by the present invention, the following uses a plurality of specific examples to illustrate the specific process of preparing the pre-sodiumized sodium ion battery negative electrode material using the method provided by the above embodiment of the present invention, as well as the electrochemical properties of the prepared pre-sodiumized sodium ion battery negative electrode material.

[0049] Example 1

[0050] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0051] In the second step, 100 g of walnut shell precursor and 300 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0052] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment at a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 800°C for 6 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0053] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is continued to be kept at 800°C for 6 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0054] Afterwards, the prepared pre-sodiumized sodium ion battery negative electrode material was used as the negative electrode plate of the sodium ion battery, and a button half-cell was assembled for testing, as follows:

[0055] First, add 0.375g of carboxymethyl cellulose (CMC) to 15g of deionized water for dispersion, the dispersion disk speed is 2000r / min, the time is 30min, and a clear glue solution is obtained. Add 0.3g of conductive carbon black (SP) to the glue solution and continue to disperse, the dispersion disk speed is 2000r / min, the time is 40min, and a slurry is obtained. Add 14.175g of the prepared pre-sodiumized sodium ion battery negative electrode material to the slurry and continue to disperse, the dispersion disk speed is 2000r / min, the time is 40min, and then add an appropriate amount of water to adjust the viscosity to 3000mPa.s. Then add 0.375g of styrene-butadiene rubber (SBR) emulsion (solid content is 40%) to the slurry, the dispersion disk speed is 1000r / min, and the time is 30min. Then reduce the dispersion disk speed to 500r / min, slowly stir for 30min, and take out the slurry. The slurry was coated on an aluminum foil current collector and dried in a vacuum oven at 80° C. for 12 hours. The dried electrode was cut to serve as the negative electrode of the sodium ion battery.

[0056] Then, the button-type sodium ion half-cell is assembled using the negative electrode sheet. The aqueous electrolyte of the button-type sodium ion half-cell is 1 mol / L sodium hexafluorophosphate (NaPF6), and the solvent of the electrolyte is dimethyl ether (DME). The counter electrode is a sodium sheet.

[0057] Finally, electrochemical tests were performed to evaluate the electrochemical performance. The test conditions were: charge cut-off voltage was 2V, discharge cut-off voltage was 0V, and current density was 0.1C.

[0058] Example 2

[0059] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0060] In the second step, 100 g of walnut shell precursor and 300 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0061] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment at a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm for 2 hours at a temperature of 1000°C to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0062] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 800°C for 6 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0063] The assembly and testing of button-type half-cells are the same as those in Example 1.

[0064] Example 3

[0065] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0066] In the second step, 100 g of walnut shell precursor and 300 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0067] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment under a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 600°C for 12 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0068] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 800°C for 6 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0069] The assembly and testing of button-type half-cells are the same as those in Example 1.

[0070] Example 4

[0071] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0072] In the second step, 100 g of walnut shell precursor and 100 g of sodium hydroxide are weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0073] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment under a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 800°C for 12 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0074] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 800°C for 6 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0075] The assembly and testing of button-type half-cells are the same as those in Example 1.

[0076] Example 5

[0077] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0078] In the second step, 100 g of walnut shell precursor and 300 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0079] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment under a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 800°C for 6 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0080] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 900°C for 1 hour, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0081] The assembly and testing of button-type half-cells are the same as those in Example 1.

[0082] Comparative Example 1

[0083] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0084] In the second step, 100 g of walnut shell precursor and 300 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0085] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment at a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 800°C for 6 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0086] However, after the pre-sodium porous carbon material is taken out, it will spontaneously combust, so the button half-cell cannot be assembled and tested.

[0087] Comparative Example 2

[0088] In the first step, the walnut shell is subjected to high-temperature carbonization treatment at 900° C. for 6 hours under a nitrogen atmosphere to obtain a walnut shell precursor.

[0089] In the second step, 100 g of walnut shell precursor and 20 g of sodium hydroxide are weighed, mixed and ground to obtain a sodium hydroxide / walnut shell precursor mixed powder.

[0090] The third step is to place the sodium hydroxide / walnut shell precursor mixed powder in a rotary furnace for activation treatment at a nitrogen atmosphere with a gas flow rate of 1 L / min, and keep it warm at 800°C for 6 hours to decompose the sodium hydroxide and reduce it by the carbon in the walnut shell precursor. At the same time, the walnut shell precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0091] Afterwards, the prepared pre-sodium porous carbon material was used to assemble and test button-type half-cells, and the assembly and testing were the same as in Example 1.

[0092] according to Figure 2 It can be seen that the charge and discharge curves of the material prepared by the present invention are not abnormal compared with those of Comparative Example 2, indicating that the pre-sodium method does not produce other side reactions.

[0093] according to Figure 3As shown, the first efficiency of Comparative Example 2 is only 43.28%. This is because the pre-sodiumized sodium-ion battery negative electrode material obtained by the preparation method of the present invention successfully achieves the pre-sodium effect and improves the low first efficiency problem of the sodium-ion battery negative electrode material. Although Comparative Example 2 was able to successfully prepare the pre-sodium porous carbon material by reducing the ratio of sodium hydroxide to walnut shell precursor, since it did not go through the chemical vapor deposition process, there was no additional protection for the active sodium in the pores, resulting in a poor pre-sodium effect, so that the first efficiency of the button half-battery assembled using this material was not improved and remained at a low level.

[0094] according to Figure 4 It can be seen that due to the pre-sodium effect, the initial voltage of Examples 1-5 is lower than that of Comparative Example 2, which is also one of the signs of successful pre-sodium. This shows that the increase in the sodium content in the battery system can effectively compensate for the consumption of sodium by SEI film formation and irreversible adsorption in the material. Therefore, the preparation method of the present invention is an effective method for improving the initial effect.

[0095] Example 6

[0096] In the first step, chitosan is subjected to high temperature carbonization treatment at 800° C. for 12 hours under an argon atmosphere to obtain a chitosan precursor.

[0097] In the second step, 100 g of chitosan precursor and 1000 g of sodium hydroxide were weighed, mixed and ground to obtain sodium hydroxide / chitosan precursor mixed powder.

[0098] The third step is to place the sodium hydroxide / chitosan precursor mixed powder in a rotary furnace for activation treatment at a temperature of 500°C for 12 hours under an argon atmosphere with a gas flow rate of 0.8L / min, so that the sodium hydroxide is decomposed and reduced by the carbon in the chitosan precursor. At the same time, the chitosan precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0099] In the fourth step, argon is continued to be introduced into the rotary kiln at a gas flow rate of 0.2 L / min and ethylene is introduced at a gas flow rate of 0.6 L / min according to a volume ratio of argon to ethylene of 1:3. The temperature is kept at 500°C for 12 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0100] Example 7

[0101] In the first step, the graphene is subjected to high-temperature carbonization treatment at 1000°C for 6 hours in a helium atmosphere to obtain a graphene precursor.

[0102] In the second step, 100 g of the graphene precursor and 50 g of sodium hydroxide are weighed, mixed and ground to obtain a sodium hydroxide / graphene precursor mixed powder.

[0103] The third step is to place the sodium hydroxide / graphene precursor mixed powder in a rotary furnace for activation treatment at a helium atmosphere with a gas flow rate of 1.2 L / min, and keep it warm at 1200°C for 1 hour to decompose the sodium hydroxide and reduce it with the carbon in the graphene precursor. At the same time, the graphene precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0104] In the fourth step, helium is continuously introduced into the rotary kiln at a gas flow rate of 0.6 L / min and propylene is introduced at a gas flow rate of 0.2 L / min according to a volume ratio of helium to propylene of 3:1. The temperature is kept at 700°C for 8 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0105] Example 8

[0106] In the first step, the phenolic resin is subjected to high-temperature carbonization treatment at 1500° C. for 3 hours in a helium atmosphere to obtain a phenolic resin precursor.

[0107] In the second step, 100 g of the phenolic resin precursor and 25 g of sodium hydroxide are weighed, mixed and ground to obtain a sodium hydroxide / phenolic resin precursor mixed powder.

[0108] The third step is to place the sodium hydroxide / phenolic resin precursor mixed powder in a rotary furnace for activation treatment under a helium atmosphere with a gas flow rate of 0.9 L / min, and keep it warm at a temperature of 1000°C for 5 hours to decompose the sodium hydroxide and reduce it with the carbon in the phenolic resin precursor. At the same time, the phenolic resin precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0109] In the fourth step, helium is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and acetylene is introduced at a gas flow rate of 1 L / min according to a volume ratio of helium to acetylene of 1:5. The temperature is kept at 850°C for 9 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0110] Example 9

[0111] In the first step, the lignin is subjected to high-temperature carbonization treatment at 950° C. for 8 hours under an argon atmosphere to obtain a lignin precursor.

[0112] In the second step, 100 g of lignin precursor and 20 g of sodium hydroxide were weighed, mixed and ground to obtain a sodium hydroxide / lignin precursor mixed powder.

[0113] In the third step, the sodium hydroxide / lignin precursor mixed powder is placed in a rotary kiln for activation treatment at a temperature of 900°C for 8 hours under a nitrogen atmosphere with a gas flow rate of 1.1 L / min, so that the sodium hydroxide is decomposed and reduced by the carbon in the lignin precursor. At the same time, the lignin precursor is etched to form a porous structure to obtain a pre-sodium porous carbon material.

[0114] In the fourth step, argon is introduced into the rotary kiln at a gas flow rate of 0.8 L / min and carbon monoxide is introduced at a gas flow rate of 0.2 L / min according to a volume ratio of argon to carbon monoxide of 4:1. The temperature is kept at 600°C for 10 hours, and the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

[0115] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a pre-sodiumized sodium ion battery negative electrode material, characterized in that: The preparation method comprises: The carbon precursor and sodium hydroxide are mixed and ground according to a certain mass ratio to obtain a mixed powder; Under an inert atmosphere, placing the mixed powder in a rotary kiln for activation treatment, so that the sodium hydroxide is decomposed and reduced by the carbon in the carbon precursor, and at the same time, etching the carbon precursor so that the carbon precursor forms a porous structure to obtain a pre-sodium porous carbon material; In the rotary kiln, the pre-sodium porous carbon material is coated by chemical vapor deposition to obtain a pre-sodiumized sodium ion battery negative electrode material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon precursor to sodium hydroxide is 1:10-5:

1.

3. The preparation method according to claim 1, characterized in that: The temperature of the activation treatment is 500° C.-1200° C., and the time of the activation treatment is 1 hour-12 hours.

4. The preparation method according to claim 1, characterized in that: The carbon precursor includes walnut shell, coconut peel, nut shell, kelp, grapefruit peel, lotus root, eggshell membrane, cork, coconut shell, straw, starch, renewable cotton, polyaniline, lignin, cellulose, hemicellulose, honeycomb briquettes, chitosan, asphalt, phenolic resin, glucose, magnesium gluconate, polyvinyl pyrrolidone, graphene oxide, graphene, xylose, epoxy resin, petroleum coke or one or more products of the above substances after high-temperature treatment; wherein the temperature of the high-temperature treatment is 800°C-1800°C.

5. The preparation method according to claim 1, characterized in that: The gas for chemical vapor deposition includes a carbon source gas and a protective gas; wherein the volume ratio of the carbon source gas to the protective gas is 1:5-5:

1.

6. The preparation method according to claim 1, characterized in that: The carbon source gas is one or more of methane, acetylene, ethylene, propylene or carbon monoxide; the protective gas is one or more of nitrogen, helium or argon.

7. The preparation method according to claim 1, characterized in that: The conditions of the chemical vapor deposition are: deposition temperature of 500° C.-900° C., and deposition time of 0.5 hour-12 hours.

8. A pre-sodiumized sodium ion battery negative electrode material, characterized in that: The pre-sodiumized sodium ion battery negative electrode material is prepared by the preparation method described in any one of claims 1 to 7 above.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the pre-sodiumized sodium ion battery negative electrode material according to claim 8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Camphor tree-base porous activated carbon, preparation method thereof and application of camphor tree-base porous activated carbon in electrochemical energy storage

    CN108715447A

  • Sodium ion battery negative electrode material and preparation method thereof

    CN109742399A

  • Novel sodium-ion battery negative electrode material and preparation method thereof

    CN112490412A

  • Hard carbon negative electrode composite material and preparation method and application thereof

    CN113184828A

  • Negative electrode material and preparation method therefor, and lithium-ion battery

    WO2023125171A1

Cited By

  • Silicon-carbon composite material, preparation method thereof and lithium ion battery comprising silicon-carbon composite material

    CN122117875A